PENGARUH PARTISIPASI ANGGARAN, PERSEPSI KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL, DAN GOAL COMMITMENT TERHADAP KINERJA DINAS - Ulupui, I. G. K. (KINERJA, 2005)
This research examined the effects of budget participation on performance of offices on duty in Badung Regency. The offices turned out to be executive elements of local government directly involved in budget preparation and served as a working unit providing public services. Furthermore, the research looked for the effects of the distributive and procedural justice perception, and goal commitment on the performance. Samples taken in the research involved offices in Badung Regency. Unit analysis were the heads of the offices, since they were mostly involved in budget processing in the offices. Data were collected through questionnaires and interviews. Out of 87 questionnaires sent, only 79 could be processed in a regression method. The results showed that budget participation had a significant effect on performance. This research also proved that justice perception, especially procedural justice, showed a positive and significant effect, while distributive justice perception showed an in-significant effect. It indicates that the higher justice perception, the higher performance of offices. On the other hand, the relationship between goal commitment and budget participation was negative and significant. It is not in line with the research of Wentzel (2002), and Locke & Latham (1990), which said that individual’s performance would be better when it had a commitment to reach special goals.Keywords: budget participation, distributive justice, procedural justice, budget performance.